Effects of resistance training using known vs. unknown loads on eccentric phase adaptations and concentric velocity - Hernandez-Davo, J. L.; Sabido, R.; Behm, D. G.; Blazevich, A. J. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The aims of this study were to compare both eccentric- and concentric-phase adaptations in highly-trained handball players to 4 weeks of twice-weekly rebound bench press throw training with varying loads (30%, 50% and 70% of 1-repetition maximum [1-RM]) using either known (KL) or unknown (UL) loads, and to examine the relationship between changes in eccentric- and concentric-phase performance. Twenty-eight junior team-handball players were divided into two experimental groups (KL or UL) and a control group. KL subjects were told the load prior each repetition, while UL were blinded. For each repetition, the load was dropped and then a rebound bench press at maximum velocity was immediately performed. Both concentric and eccentric velocity as well as eccentric kinetic energy and musculo-articular stiffness prior to the eccentric-concentric transition were measured. Results showed similar increases in both eccentric velocity and kinetic energy under the 30% 1-RM but greater improvements under 50% and 70% 1-RM loads for UL than KL. UL increased stiffness under all loads (with greater magnitude of changes). KL improved concentric velocity only under the 30% 1-RM load while UL improved under 50% and 70% 1-RM loads. Improvements in concentric movement velocity were explained moderately by changes in eccentric velocity (R2 = 0.23-0.62). Thus, UL led to greater improvements in concentric velocity, and the improvement is potentially explained by increases in the speed (as well as stiffness and kinetic energy) of the eccentric phase. Unknown load training appears to have significant practical use for the improvement of multi-joint stretch-shortening cycle movements.